2002
DOI: 10.1002/smi.946
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress in adults: prevalence and association of depression, anxiety and medication in a Swedish population

Abstract: The objectives were to measure the prevalence of perceived stress in adults and to evaluate gender and age differences in stress level. Association between perceived stress and depression, anxiety and medication was also studied. A total of 1275 subjects (581 men and 694 women) were randomly selected in equal age groups. Perceived stress was measured with the Perceived Stress Questionnaire (PSQ). Two PSQ cut-off scores, moderate and high stress level, were yielded by using mean score and standard deviation. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
5
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 18 publications
14
158
5
4
Order By: Relevance
“…On the other hand, an advantage of this home/webbased type of training is that in practice it allows for flexibility in regard to training pace (i.e., a factor that had to be restricted at present for purposes of experimental control). Finally, even though an overweight of females may generally be expected at higher perceived stress levels [21] the fact that the present sample included mainly women (90%) is of potential concern in regard to the external validity of the results.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the other hand, an advantage of this home/webbased type of training is that in practice it allows for flexibility in regard to training pace (i.e., a factor that had to be restricted at present for purposes of experimental control). Finally, even though an overweight of females may generally be expected at higher perceived stress levels [21] the fact that the present sample included mainly women (90%) is of potential concern in regard to the external validity of the results.…”
Section: Discussionmentioning
confidence: 86%
“…Even though this self-report inclusion criterion is vague, mean pretest scores, indicative of severe levels of stress (PSQ>0.45) [21], suggested that the participants were at risk of stress-related health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PSQ index, varying from 0 (the lowest level) to 1 (the highest level) is calculated by dividing the total raw score with 90 [22]. We used the estimated PSQ index of >0.34 to define moderate level of perceived stress [23].…”
Section: Evaluation Of Stressmentioning
confidence: 99%
“…In the regression model age was regarded as continuous variable. HADS-D was categorized into two groups according to the accepted "cut-off" at ≥8 points, HADS-A was categorized into two groups according to the accepted "cut-off at ≥9 points [19,20] and PSQ index was categorized into two groups according the estimated moderate level of perceived stress (PSQ index >0.34) [23]. The Hosmer-Lemeshow test was used to test the accuracy of the logistic regression model.…”
Section: Statisticsmentioning
confidence: 99%